Polymorphic avr genes in isolates of two races of Passalora fulva from Argentina - Medina, Rocío (2014)
The purpose of this work was to identify based on morphological and molecular tools the etiological agent of diseased tomatoes with leaf mould symptoms. Diseased plants were collected mainly from greenhouses within the most important production area of tomato in Argentina, the Cinturón Hortícola of Gran La Plata, Buenos Aires province, Argentina. Isolates identity was confirmed by morphological characteristics as well as the Internal Transcribed spacer sequence. Avr genes were amplified and sequenced by means of a modification of the protocol described by Stergiopoulos et al (2007). The amplicons obtained were sequenced and deposited in the NCBI GenBank. Even though P. fulva isolates were collected from different tomato cultivars and different farms, they belong either to race 0 (avr2, avr4, avr4E and avr9) or race 2 (avr4, avr4E and avr9) The avr4 sequences included transitions, transversions and insertions. While the two other genes of the isolates from Argentina avr 4E and avr 9, presented transitions and transversions and only one transversion, respectively. Although we have not studied yet the biological implications of these changes, we found that though the number of races identified by now is only two, the population of the fungus appears to be evolving therefore new races or more virulent isolates might arise.